ANALISIS POTENSI AIR TERJUN TUJUH TINGKAT BATANG KOBAN LUBUK AMBACANG SEBAGAI DAERAH EKOWISATA - Anisaldi Anisaldi; Yusni Ikhwan Siregar; Sofyan Husein Siregar (Jurnal Ilmu Lingkungan, 2014)
Tourism Area ot Tingkat Tujuh waterfall Batang Koban is located in the village ofLubuk Ambacang sub district of Hulu Kuantan Regency of Kuantan Singingi. TourismArea of Tingkat Tujuh waterfall Batang Koban is a natural tourism destination assetwith huge potential to be developed in the midst of the construction and development ofthe region, and should be given attention optimally and sustainably toprovide benefitsof local communities, to improve the welfare of nature and the surroundingsenvironment. In the development and management of Tingkat Tujuh waterfall BatangKoban Lubuk Ambacang must be able to balance the various aspects of the interplayamong social, economic and environmental. Besides having a diversity of flora andfauna tourism area of Tingkat Tujuh waterfall Batang Koban has a uniquenessecosystem, unspoiled natural phenomena and socio-economic culture of localcommunities, which can be used as a potential in the development of ecotourism in theregion. The method used in this research is a survey method. The research wasconducted on April – May 2010. Location was determined by purposive sampling onthe grounds that this region will become the area of featured natural tourism inKuantan Singingi regency. Departing from the interests of sustainable ecotourismdevelopment, the issue that needs to be studies is, 1) Identify biophysical potential andsocio-cultural communities of tourism area to be developed into an ecotourism region2) Provide policy recommendations on the development of ecotourism in the touristareas. The results showed that Tingkat Tujuh waterfall Batang Koban LubukAmbacang has potential to be developed as ecotourism area. The advantages contain inthe Tingkat Tujuh waterfall Batang Koban Lubuk Ambacang such as uniqueness andmagnificence as well as the different charms of each level. Diversity of flora and faunadue to lie on the Bukit Barisan mountains, the originality scenery of the forest, and thewaterway with some natural charm and myths-myths that can be used as a tourismattraction. The aspects of ecotourism development techniques that can be conducted isthe appointment of the person or institution that served as a regional manager with theknowledge, skills and debriefing in waterfalls ecotourism, repair and improvement offacilities an tourism programs.